CFD Simulation Approach to Predict Fire-Influenced Domino Accident Propagation Pattern - Ahmed Malik, A. (2023)
Domino effect by fire has been known for many industrial devastations in the past records.Risk-based approaches in terms of consequence and probability are being applied to avoid and mitigate such accidents.The incident radiative heat flux triggers domino effect by fire to nearby equipment.This heat flux has been calculated using semi-empirical correlations which fail to capture full fire dynamics.Fire Dynamics Simulator (FDS) predicts time varying heat flux with well-defined fire characteristics.This study uses well valid FDS software to predict heat flux to equipment in proximity.The obtained heat flux is used to estimate the escalation probability to each tank.The results of FDS are verified with the outcomes of correlations on a tank farm case study.Wind effect is induced in order to represent a realistic scenario revealing a major alteration in domino propagation pattern.The incident heat flux due to tilted flame doubles in magnitude with a four-order increase in the escalation probability for the most affected tank, intensifying its vulnerability. Â© 2023, Institute of Technology PETRONAS Sdn Bhd.